Diseño de una guía metodológica para el proceso de planeación financiera de proyectos en empresas del sector servicios en Bogotá, D. C. (2019)
This research seeks, through the development of a methodological guide to the financial planning process of projects, to provide a set of guidelines that allow the identification of opportunities for improvement and potential benefits against aspects of the financial planning of projects in companies of the service sections in Bogota, D.C. The identified research problem focuses on specific weaknesses of conceptual and methodological aspects of the financial planning in projects in service section companies in Bogota, D.C., such as asymmetry in financial information, weaknesses in planning procedures in operations, control gaps in financial variables, among others. For the development of this thesis, a qualitative approach with descriptive scope is applied to conduct review of existing literature regarding the financial planning process of projects and suggesting a process to follow. A probing of 38 companies in the sector studied analyses the suggested process and deficiencies found in the problem tree. Subsequently, the methodological guide to the financial planning process of projects in the service section companies in Bogota, D.C., is designed using the descriptive study, since according to Tam, Vera and Oliveros (2008), the descriptive transectional research it seeks to measure relevant variables, which is reflected in the development of the guide. The methodological guide is then validated with experts, specifying important properties and characteristics of the investigated process. Through the methodological guide for PPFP, language is unified between the different areas of the organization in accordance with the International Financial Reporting Standards (IFRS), which generates symmetry of the financial information in the companies to be applied. Compiling existing literature defines seven main stages of the project financial planning process such as: defining the organization's strategy, identifying and aligning the project strategically, formulating, evaluating, executing, operating and liquidate the project. The financial planner of mainly mipymes companies, has a way forward with each of the stages, financial statement projection techniques, cash budget, budgeting exercises and evaluation metrics, all changing according to the stage. Each stage has different goals because the product of financial planning is different. The guide is based on different conceptual and validation steps that make it a reliable, efficient and effective document.